HUBUNGAN KENAIKAN BERAT BADAN DENGAN LAMA PEMAKAIAN KONTRASEPSI SUNTIK 3 BULAN - Apria Wilinda Sumantri (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
Family planning is the most basic and primary preventive health care effort, as well as theprevention of death. Family planning services can be done with the use of contraceptives.Contraceptive 3-month injection is a type of fluid injected into the female body intramuscularly (3months) . To know weigh relationhip increasemen wingh the use of 3 month injectable villagelaya working area UPTD community health center tanjung agung baturaja barat 2018 year. ofAnalytic survey research with cross sectional approach. sample research taken by accidentalsampling with a large sampe of 30 respondents Data can be by using the observation instrument,after all data collected then performed data processing using SPSS program version 22, ..Univariate analysis result, from 80 respondents found 57 (71,2%) using injectable contraception,43 (75,4%) who gained weight, 14 (24,6%) who did not gain weight. From result of statisticanalysis obtained pvalue: 0,02. The existence of 3 Months KB Injections Connection with WeightGain Increase in Laya Work area UPTD Puskesmas Tanjung Agung Year 2018. Relationshipincreasment wing the use of 3 month injectable. Increasement weingh, cross sectional, statisticaltest Chi-Squeare.